Idea #4 - Region I Labor Consultant (Tufts Archival Research Center, 2007)
Memo from Dennis Dyer to Roger Mozingo recommending that the Tobacco Institute hire James Tiernan as a Region I Labor Consultant. Discusses tobacco/labor connection in New England. Proposes a consultant to meet with local labor unions, discuss issues, and introduce and pass resolutions opposing anti-tobacco proposals. Includes letter from James Tiernan outlinging his plans and listing people he will meet with.